PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017) - Asthari Oliviana; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of good corporate governance consisting of executive character, company size, independent commissioner, board of directors, audit committee, audit committee meetings, and audit quality on tax avoidance measured by ETR. The population of this study consists of manufacturing companies that listed in Indonesian Stock Exchange in the period of 2014-2017. Sample determined with purposive sampling method. Total sample of this research is 145 companies. In order to test hypothesis, the study performed multiple regression analysis. The results of this study show that only audit committee meetings and audit quality have positive effect on tax avoidance. Executive character, board of director, and audit committee have negative effect on tax avoidance. While company size and independent commissioner have no significant effect on tax avoidance.